ANALISIS KEMAMPUAN SISWA DALAM CONSTRUCTING EXPLANATIONS AND DESIGNING SOLUTIONS MATERI GERAK DAN GAYA - Tiara Obrilian Cahyanti; Sukarmin Sukarmin; Ashadi Ashadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
ANALYSIS OF THE ABILITY IN CONSTRUCTING EXPLANATIONS AND DESIGNING SOLUTIONS OF STUDENTS ON FORCE AND MOTION AbstractThis study is aimed to determine the Constructing explanations and designing solutions ability among students in Force and Motion subject. The result was analyzed by descriptive methode to describe the Constructing explanations and designing solutions ability among junior high school student. The sample of this study included 128 students of four junior high schools; SMP N 1 Jaten, SMP N 1 Kebakkramat, SMP N 3 Surakarta, and SMP N 5 Surakarta. The results showed that the ability of students in constructing explanations and designing solutions in each aspect below 55%. The percentage of the student’s Constructing explanations and designing solutions ability in each sub-subject was on the moderate category, then there should be a treatment to improve the students' Constructing explanations and designing solutions ability. AbstrakTujuan dari penelitian ini adalah untuk menentukan kemampuan siswa dalam Constructing explanations and designing solutions pada materi Gerak dan Gaya kelas VIII SMP. Penelitian ini menerapkan penelitian deskriptif yang bertujuan untuk menggambarkan kemampuan siswa dalam Constructing explanations and designing solutions. Subjek penelitian adalah 128 siswa SMP yang terdiri dari 4 sekolah yaitu SMP N 1 Jaten, SMP N 1 Kebakkramat, SMP N 3 Surakarta, dan SMP N 5 Surakarta. Hasil penelitian menunjukkan bahwa kemampuan siswa dalam constructing explanations and designing solutions pada masing-masing aspek dibawah 55%. Selain itu persentase kemampuan siswa dalam Constructing explanations and designing solutions pada masing-masing sub materi masuk dalam kategori sedang, sehingga perlu dilakukan tindakan untuk meningkatkan kemampuan siswa dalam Constructing explanations and designing solutions.